Autonomous and Autogenous Self-Healing of Freeze-Thaw Cracks of Geopolymer Concrete Containing Colemanite/Red Mud - Tanyildizi, Harun; Ziada, Mahmoud; Acik, Volkan; Uysal, Mucteba; Coskun, Ahmet (Asce-Amer Soc Civil Engineers, 2026)
This study investigated autonomous and autogenous healing of metakaolin-based geopolymer concrete exposed to the freeze-thaw cycles. Sporosarcina pasteurii was used as a healing agent in the healing process. Samples with and without the S. pasteurii bacteria were produced and cured at 20 degrees C +/- 2 degrees C for 28 days. Subsequently, these samples were exposed to freeze-thaw cycles. Then, the solutions with bacteria and bacteria-free medium were injected into the cracks. After the healing procedure, the ultrasonic pulse velocity, splitting tensile strength, mass change, capillary water absorption, and microstructure experiments were carried out on the samples. The results showed that after the autonomous and autogenous healing, the splitting tensile strength of samples containing bacteria was found to be up to 10.9% greater compared to samples without bacteria. Also, the highest ultrasonic pulse velocity and splitting tensile strength values were obtained from autogenous self-healing samples. Also, the microcomputed tomography found that the bacteria-based healing could heal 91.3% of the total porosity of the sample.
Keywords: Geopolymer concrete; Freeze-thaw; Sporosarcina pasteurii; Autonomous healing; Autogenous healing